Workplace deviantbehaviour: a review of typology of workplace deviantbehaviour - Norsilan, Ili Nabila; Omar, Zoharah; Ahmad, Aminah (IDOSI Publications, 2014)
Over the past decade, research and studies on workplace deviantbehaviour such as absenteeism, dishonesty, aggression and stealing among employees have increased along with the increase in the prevalence of deviant behaviour at workplace. Workplace deviant has been labeled with many terms and typologies. Hence, this paper discusses the concept of work place deviant and its typologies. This paper also focuses on the emerging types of deviant behaviour at work such as cyber-related deviant.